Determinants of Food Insecurity in Africa and Asia: A Comparative Analysis - Mansi Raj; B. Arulmanikandan; Pardeep Kumar Chahal; Bharat Singh; Joginder Singh Malik (Indian Journal of Extension Education, 2026)
Food insecurity remained a persistent challenge in Africa and Asia due to interacting agricultural, technological, climatic, and environmental factors. The study conducted during 2025 examined the determinants of food insecurity across selected African and Asian countries using cross-country data from 2020 to 2024. It assessed the effects of agricultural productivity, technological adoption, research investment, climate adaptation spending, and environmental pressure on food insecurity. A quantitative cross-sectional design was employed, and data were analysed using Pearson’s correlation and multiple linear regression. The results indicated that cereal yield, precision agriculture adoption, research and development expenditure, and climate adaptation spending showed significant negative associations with food insecurity. In contrast, greenhouse gas emissions and higher agricultural value added exhibited positive associations. The regression model explained 82 per cent of the variation in food insecurity, indicating strong explanatory power. The findings demonstrated that productivity enhancement, technological diffusion, research investment, and climate-responsive measures were critical determinants of reduced food insecurity across the selected countries.